Assessment of Agricultural Needs in African, Caribbean and Pacific States: Phase 1: Caribbean: Country Study: Grenada - Church, Michael (Technical Centre for Agricultural and Rural Cooperation, 2006)
This study, commissioned by CTA, details the information needs, and priorities of key agricultural institutions in Grenada